2022
DOI: 10.15561/26649837.2022.0503
|View full text |Cite
|
Sign up to set email alerts
|

Perceived barriers to adopting information and communication technology in physical education

Abstract: Background and Study Aim. The use of Information and Communication Technologies (ICTs) in Physical Education (PE) brings the science of sports to life by combining physical and mental activity. It also helps students focus better on practical and theoretical work. The purpose of this study was to investigate the perceived barriers to adopting ICTs in PE lessons among high school teachers in Malaysia. Material and Methods. A total of 112 Physical Education teachers were selected by stratified random sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Several studies have confirmed that PE teachers are still experiencing problems in utilizing information technology (Friskawati et al, 2019;Irwahand et al, 2022). Therefore, the latest study by recommended that teachers improve the quality of learning by integrating information technology (Blegur, Lumba, et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have confirmed that PE teachers are still experiencing problems in utilizing information technology (Friskawati et al, 2019;Irwahand et al, 2022). Therefore, the latest study by recommended that teachers improve the quality of learning by integrating information technology (Blegur, Lumba, et al, 2023).…”
Section: Discussionmentioning
confidence: 99%